2001
DOI: 10.1074/jbc.m100314200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ceramide in Mediating the Inhibition of Telomerase Activity in A549 Human Lung Adenocarcinoma Cells

Abstract: This study was designed to analyze whether ceramide, a bioeffector of growth suppression, plays a role in the regulation of telomerase activity in A549 cells. Telomerase activity was inhibited significantly by exogenous C 6 -ceramide, but not by the biologically inactive analog dihydro-C 6 -ceramide, in a time-and dose-dependent manner, with 85% inhibition produced by 20 M showing that the increased endogenous ceramide is sufficient for telomerase inhibition. Moreover, treatment of A549 cells with daunorubicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 52 publications
7
98
0
1
Order By: Relevance
“…Multiple lines of evidence have demonstrated the ability of endogenous ceramide to inhibit telomerase activity in A549 cells [87,88]. Moreover, exogenous C 6 -ceramide was also shown to inhibit telomerase, but interestingly, it was found that these actions are due to generation of endogenous ceramide in a process that requires recycling of the sphingosine backbone of C 6 -ceramide through deacylation followed by reacylation to mainly C 16:0 ceramide [18].…”
Section: -3 Telomerase Activity and Recycling Of Short-chain Ceramidementioning
confidence: 99%
“…Multiple lines of evidence have demonstrated the ability of endogenous ceramide to inhibit telomerase activity in A549 cells [87,88]. Moreover, exogenous C 6 -ceramide was also shown to inhibit telomerase, but interestingly, it was found that these actions are due to generation of endogenous ceramide in a process that requires recycling of the sphingosine backbone of C 6 -ceramide through deacylation followed by reacylation to mainly C 16:0 ceramide [18].…”
Section: -3 Telomerase Activity and Recycling Of Short-chain Ceramidementioning
confidence: 99%
“…One microgram of total RNA, isolated using an RNA isolation kit (Qiagen, Valencia, CA), was used in reverse transcription reactions as described (22). The resulting total cDNA was then used in the quantitative real-time PCR (Q-RT-PCR) to measure the mRNA levels using TaqMan gene expression kit (Applied Biosystems, Foster City, CA) with ABI 7300 Q-PCR system.…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
“…The protein levels of human LASS1 and LASS6 were detected by Western blotting using mouse polyclonal antibodies (Abnova) as described previously (22).…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Telomerase downregulators include the estrogen analogue tamoxifen, 12 differentiation inducers such as retinoic acid, 13,14 DNA-interacting agents daunorubicin, doxorubicin and cisplatin. [15][16][17][18][19][20] However, some of these drugs have complex effects on telomerase activity in treated cells. For example, human testicular cancer cells treated with lethal doses (100 m) of the DNA cross-linker cisplatin exhibit decreased telomerase activity.…”
Section: Introductionmentioning
confidence: 99%